Extraction, characterization and anti-oxidant activity of polysaccharide from red Panax ginseng and Ophiopogon japonicus waste - Kang, Jia; Zhao, Jue; He, Lan-Fang; Li, Li-Xia; Zhu, Zhong-Kai; Tian, Meng-Liang (Frontiers in Nutrition, 2023)
Red ginseng and Ophiopogon japonicus are both traditional Chinese medicine, and also used as food in China for thousands years. Those two herbs were frequently used in many traditional Chinese patent medicine, the carbohydrate composition of these two herbs was normally not used during the production of patent medicine, such as shenmai injection, which resulting in a big waste of carbohydrate. In this study, the extraction conditions were optimized by response surface methodology, the shenmai injection waste polysaccharide was extracted by using boiling distilled water under the optimized conditions, shenmai injection waste polysaccharide (SMP) were hereby obtained. SMP was further purified by anion exchange chromatography and gel filtration and an neutral polysaccharide fraction SMP-NP and an acidic polysaccharide fraction SMP-AP were obtained. The results of structure elucidation indicated that SMP-NP was a type of levan, and SMP-AP was a typical acidic polysaccharide. SMP-NP exhibited potential stimulation activity on the proliferation of five different Lactobacilli strains. SMP-AP could promote the antioxidant defense of IPEC-J2 cells. These finding suggested that Shenmai injection waste could be used as resource for prebiotics and antioxidants.